Isolasi, Komponen Peptida Bioaktif yang Terkandung Dalam Kasein Susu - Helmi M. Yahya; Amhar Abubakar (Agricultural Faculty, 2000)
ABSTRACT. The production of Casein hydrolysate with an extracellular proteinase from Lactobacillus helveticus CP790, was fractionated by two-step reverse phase heigh performance liquid chromatography. Only 1 fraction showed antihypertensive activity as measured by systolic blood pressure in spontaneously hypertensive rats after oral adsministration. Ten peptides in the fraction were further purified and identified by analisys of amino acid sequences. Each identified peptide was chemically synthesized, and the ant.ihypertensive activity of each peptide was evaluated in spontaneously hypertensive rats. The synthetic peptide with a sequence of Lys-Val-Leu-Pro-Val-Pro-Gln, found in -casein, indicated strong antihypertensive activity from 2 to 10 h after oral adsministration of 2 mg of peptide/kg of BW, and the effect was maximal at 6 h after oral adsministration. Moreover, the antihypertensive effect of the peptide was dependent on the dosage of peptide from 0.5 to 2 mg o peptide/kg of BW.